2003
DOI: 10.1037/0096-1523.29.1.106
|View full text |Cite
|
Sign up to set email alerts
|

When the target becomes the mask: Using apparent motion to isolate the object-level component of object substitution masking.

Abstract: J. T. Enns and V. Di Lollo (1997) discovered a new form of visual masking that they labeled object substitution masking (OSM). OSM occurs when 4 dots, presented around a target, trail in the display after target offset. The present study showed that the physical presence of the masking dots after target offset is not necessary for OSM. Instead, the continued presence of a changing high-level representation associated with the target suffices to yield OSM. Apparent motion was used to define such representation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
241
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 110 publications
(260 citation statements)
references
References 49 publications
17
241
2
Order By: Relevance
“…Consistent with this, it has been found that shape and surface similarity seem to influence the visibility of the central stimulus in the standing wave display (Enns, 2002;Pilling & Gellatly, 2009;Werner, 1935). In addition, if the scene is interpreted as the central bar being a previous instantiation of the flanking bars, it is expected that apparent motion should be seen between them (Lleras & Moore, 2003). Taken together, the more similar the central bar and flankers are, the more likely they are to be integrated, and therefore observers should perceive more motion.…”
Section: Tasksupporting
confidence: 51%
See 1 more Smart Citation
“…Consistent with this, it has been found that shape and surface similarity seem to influence the visibility of the central stimulus in the standing wave display (Enns, 2002;Pilling & Gellatly, 2009;Werner, 1935). In addition, if the scene is interpreted as the central bar being a previous instantiation of the flanking bars, it is expected that apparent motion should be seen between them (Lleras & Moore, 2003). Taken together, the more similar the central bar and flankers are, the more likely they are to be integrated, and therefore observers should perceive more motion.…”
Section: Tasksupporting
confidence: 51%
“…This account relies on the assumption that representational updating is mediated through object representations (Enns, Lleras, & Moore, 2008;Lleras & Moore, 2003;Moore & Lleras, 2005;Moore, Mordkoff, & Enns, 2007). Given the right timing between the central bar and flankers, the visual contour formation.…”
mentioning
confidence: 99%
“…Masking was reduced so long as the masks were briefly (133 ms) previewed. Lleras and Moore (2003) argued that two different components must contribute to the total interference in OSM: low-level backward masking and interference at higher-, object-level representations. A critical differentiation between a lower-level and a higher-level representation is whether the representation is tied to a specific location: the exact location will not be crucial if the underlying mechanisms are high-level.…”
Section: Methodsmentioning
confidence: 99%
“…To test whether interference actually takes place at this object-token level of representation in OSM, Lleras and Moore (2003) manipulated the location of the mask and created object-token representations with apparent motion. The task was to identify and report the black target among the seven other grey distractors (see Figure 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation